Understanding complex drivers of wildlife crime to design effective conservation interventions. Issue 6 (3rd July 2019) - Travers, Henry; Archer, Lucy J.; Mwedde, Geoffrey; Roe, Dilys; Baker, Julia; Plumptre, Andrew J.; Rwetsiba, Aggrey; Milner‐Gulland, E.J.
Abstract: In conservation understanding the drivers of behavior and developing robust interventions to promote behavioral change is challenging and requires a multifaceted approach. This is particularly true for efforts to address illegal wildlife use, where pervasive—and sometimes simplistic—narratives often obscure complex realities. We used an indirect questioning approach, the unmatched count technique, to investigate the drivers and prevalence of wildlife crime in communities surrounding 2 national parks in Uganda and combined scenario interviews and a choice experiment to predict the performance of potential interventions designed to tackle these crimes. Although poverty is often assumed to be a key driver of wildlife crime, we found that better‐off households and those subject to human–wildlife conflict and those that do not receive any benefits from the parks' tourism revenue sharing were more likely to be involved in certain types of wildlife crime, especially illegal hunting. The interventions predicted to have the greatest impact on reducing local participation in wildlife crime were those that directly addressed the drivers including, mitigating damage caused by wildlife and generating financial benefits for park‐adjacent households. Our triangulated approach provided insights into complex and hard‐to‐access behaviors and highlighted the importance of going beyond single‐driver narratives. Abstract : Article impact statement : Interventions to reduce wildlife crime are most effective when addressing the underlying motivations of people involved in those crimes. Abstract : Comprensión de los Conductores Complejos de los Delitos con Vida Silvestre para Diseñar Intervenciones Efectivas de Conservación Resumen: En la conservación, la comprensión de los conductores del comportamiento y el desarrollo de intervenciones sólidas para promover cambios en el comportamiento es un reto que requiere de una estrategia multifacética. Esto es particularmente cierto para los esfuerzos que se realizan para tratar el uso ilegal de la fauna, en donde las narrativas generalizadas – y en algunas ocasiones simples – comúnmente ocultan las realidades complejas. Usamos una estrategia de cuestionamiento indirecto, la técnica de conteo sin par, para investigar los conductores y la prevalencia de los delitos con fauna en las comunidades que rodean a dos parques naciones en Uganda, así como entrevistas de escenario combinado y un experimento de elección para predecir el desempeño de las intervenciones potenciales diseñadas para acabar con estos delitos. Aunque frecuentemente se asume a la pobreza como un conductor importante de los delitos con fauna, encontramos que los hogares con mayor probabilidad de estar involucrados en ciertos tipos de delitos, especialmente la cacería ilegal, son los que se encuentran en mejores condiciones, están sujetos al conflicto humano‐fauna y los que no reciben beneficio alguno de las ganancias del turismo en los parques. Las intervenciones que se pronosticó tendrían el mayor impacto en la reducción de la participación local dentro del delito con fauna fueron aquellas que trataron directamente con los conductores, incluyendo la mitigación del daño causado por la fauna y la generación de beneficios económicos para los hogares circundantes al parque. Nuestra estrategia triangulada proporcionó percepciones hacia los comportamientos complejos y de difícil acceso y resaltó la importancia de ir más allá de las narrativas unifactoriales. 摘要: 在保护中理解行为背后的驱动力并发展有力的干预措施以促进行为转变是一项重大的挑战, 需要采取多方面的方法来应对, 而在野生动物的非法利用问题上尤其如是。然而, 目前流行且有时甚至过于简单的方法, 往往会掩盖复杂的事实。我们用一种间接询问 （即不匹配计数） 的方法, 调查了乌干达两个国家公园周围社区的野生动物犯罪驱动力和发生率, 并结合情景访谈和选择实验预测了旨在应对这些犯罪的潜在干预措施的效果。结果表明, 虽然贫穷常常被认为是驱动野生动物犯罪的关键因素, 但实际上比较富裕的家庭、遭受人兽冲突的家庭和那些没有从国家公园的旅游收入中获益的家庭才最有可能参与特定类型的野生动物犯罪, 特别是非法捕猎。因此, 那些预计能最大程度减少当地野生动物犯罪的干预措施, 应直接针对那些引起野生动物犯罪的驱动因素, 包括减轻野生动物造成的破坏、为毗邻国家公园的家庭创造经济利益等等。我们的三边分析方法有助于深入理解复杂且难以获知的行为, 同时强调了在理解这些问题时采用超越单一驱动力分析的重要性。【翻译: 胡怡思; 审校: 聂永刚】